Large-scale analysis of high-speed atomic force microscopy data sets using adaptive image processing - Erickson, Blake W.; Coquoz, Séverine; Adams, Jonathan D.; Burns, Daniel J.; Fantner, Georg E. (Beilstein Journal of Nanotechnology, 2012)
Modern high-speed atomic force microscopes generate significant quantities of data in a short amount of time. Each image in the sequence has to be processed quickly and accurately in order to obtain a true representation of the sample and its changes over time. This paper presents an automated, adaptive algorithm for the required processing of AFM images. The algorithm adaptively corrects for both common one-dimensional distortions as well as the most common two-dimensional distortions. This method uses an iterative thresholded processing algorithm for rapid and accurate separation of background and surface topography. This separation prevents artificial bias from topographic features and ensures the best possible coherence between the different images in a sequence. This method is equally applicable to all channels of AFM data, and can process images in seconds.
Keywords: adaptive algorithm; artifact correction; atomic force microscopy; high-speed atomic force microscope; image processing

(untitled) - Binnig, G.; Quate, C. F.; Gerber, C. (Phys. Rev. Lett., 1986)

(untitled) - Czajkowsky, D. M.; Sheng, S.; Shao, Z. (J. Mol. Biol., 1998)

(untitled) - Scheuring, S.; Müller, D. J.; Ringler, P.; Heymann, J. B.; Engel, A. (J. Microsc. (Oxford, U. K.), 1999)

(untitled) - Scheuring, S.; Ringler, P.; Borgnia, M.; Stahlberg, H.; Müller, D. J.; Agre, P.; Engel, A. (EMBO J., 1999)

(untitled) - Müller, D. J.; Fotiadis, D.; Scheuring, S.; Müller, S. A.; Engel, A. (Biophys. J., 1999)

(untitled) - Müller, D. J.; Heymann, J. B.; Oesterhelt, F.; Möller, C.; Gaub, H.; Büldt, G.; Engel, A. (Biochim. Biophys. Acta, Bioenerg., 2000)

(untitled) - Hassenkam, T.; Fantner, G. E.; Cutroni, J. A.; Weaver, J. C.; Morse, D. E.; Hansma, P. K. (Bone, 2004)

(untitled) - Czajkowsky, D. M.; Hotze, E. M.; Shao, Z.; Tweten, R. K. (EMBO J., 2004)

(untitled) - Lodowski, D. T.; Salom, D.; Le Trong, I.; Teller, D. C.; Ballesteros, J. A.; Palczewski, K.; Stenkamp, R. E. (J. Struct. Biol., 2007)

(untitled) - Casuso, I.; Kodera, N.; Le Grimellec, C.; Ando, T.; Scheuring, S. (Biophys. J., 2009)

(untitled) - Picas, L.; Montero, M. T.; Morros, A.; Cabañas, M. E.; Seantier, B.; Milhiet, P.-E.; Hernández-Borrell, J. (J. Phys. Chem. B, 2009)

(untitled) - Czajkowsky, D. M.; Shao, Z. (Proc. Natl. Acad. Sci. U. S. A., 2009)

Scanning Force Microscopy of Polymers - Schönherr, H.; Vancso, G. J. (Atomic Force Microscopy in Practice, 2010)

Lipid Rafts - Burns, A. R. (Atomic force microscopy of lipid domains in supported model membranes, 2007)

(untitled) - Venkataraman, S. S.; Allison, D. P.; Qi, H.; Morrell-Falvey, J. L.; Kallewaard, N. L.; Crowe, J. E., Jr; Doktycz, M. J. (Ultramicroscopy, 2006)

(untitled) - Bickmore, B. R.; Rufe, E.; Barrett, S.; Hochella, M. F., Jr (Geol. Mater. Res., 1999)

Proceedings of the 15th IEEE International Conference on Image Processing - Tsaftaris, S. A.; Zujovic, J.; Katsaggelos, A. K. (Automated line flattening of Atomic Force Microscopy images, 2008)

(untitled) - Giocondi, M.-C.; Milhiet, P. E.; Dosset, P.; Le Grimellec, C. (Biophys. J., 2004)

(untitled) - Richter, R. P.; Brisson, A. R. (Biophys. J., 2005)

(untitled) - Watari, F. (J. Electron Microsc., 2005)

(untitled) - Kindt, J. H.; Thurner, P. J.; Lauer, M. E.; Bosma, B. L.; Schitter, G.; Fantner, G. E.; Izumi, M.; Weaver, J. C.; Morse, D. E.; Hansma, P. K. (Nanotechnology, 2007)

(untitled) - Blanchette, C. D.; Lin, W.-C.; Orme, C. A.; Ratto, T. V.; Longo, M. L. (Langmuir, 2007)

(untitled) - Blanchette, C. D.; Orme, C. A.; Ratto, T. V.; Longo, M. L. (Langmuir, 2008)

(untitled) - Erickson, B.; DiMaggio, S. C.; Mullen, D. G.; Kelly, C. V.; Leroueil, P. R.; Berry, S. A.; Baker, J. R., Jr; Orr, B. G.; Banaszak Holl, M. M. (Langmuir, 2008)

(untitled) - Ando, T.; Kodera, N.; Takai, E.; Maruyama, D.; Saito, K.; Toda, A. (Proc. Natl. Acad. Sci. U. S. A., 2001)

(untitled) - Hansma, P. K.; Schitter, G.; Fantner, G. E.; Prater, C. B. (Science, 2006)

(untitled) - Milhiet, P.-E.; Yamamoto, D.; Berthoumieu, O.; Dosset, P.; Le Grimellec, C.; Verdier, J.-M.; Marchal, S.; Ando, T. (PLoS One, 2010)

(untitled) - Kodera, N.; Yamamoto, D.; Ishikawa, R.; Ando, T. (Nature, 2010)

(untitled) - Fantner, G. E.; Barbero, R. J.; Gray, D. S.; Belcher, A. M. (Nat. Nanotechnol., 2010)

(untitled) - Högström, R.; Korpelainen, V.; Riski, K.; Heinonen, M. (Metrologia, 2010)

(untitled) - Kienberger, F.; Pastushenko, V. P.; Kada, G.; Puntheeranurak, T.; Chtcheglova, L.; Riethmueller, C.; Rankl, C.; Ebner, A.; Hinterdorfer, P. (Ultramicroscopy, 2006)

(untitled) - Pfeifer, T.; Freudenberg, R.; Dussler, G.; Bröcher, B. (Measurement, 2001)

(untitled) - Vorburger, T. V.; Dagata, J. A.; Wilkening, G.; Lizuka, K.; Thwaite, E. G.; Lonardo, P. (CIRP Ann., 1997)

(untitled) - Girard, P. (Nanotechnology, 2001)

(untitled) - Starink, J. P. P.; Jovin, T. M. (Surf. Sci., 1996)

(untitled) - Chen, S.-W. W.; Pellequer, J.-L. (BMC Struct. Biol., 2011)

(untitled) - Lenihan, T. G.; Malshe, A. P.; Brown, W. D.; Schaper, L. W. (Thin Solid Films, 1995)

(untitled) - Burns, D. J.; Youcef-Toumi, K.; Fantner, G. E. (Nanotechnology, 2011)

(untitled) - Schitter, G.; Stemmer, A. (Microelectron. Eng., 2003)

(untitled) - Schitter, G.; Stark, R. W.; Stemmer, A. (Ultramicroscopy, 2004)

(untitled) - Schitter, G.; Stemmer, A. (IEEE Trans. Control Syst. Technol., 2004)

(untitled) - Aphale, S.; Fleming, A. J.; Moheimani, S. O. R. (Micro Nano Lett., 2007)